PENGARUH PELATIHAN KEBERSYUKURAN TERHADAP PENERIMAAN ORANG TUA PADA ANAK RETARDASI MENTAL - Windarti Aji; Fuad Nashori; Indahria Sulistyarini (UIN Sunan Kalijaga, 2013)
This study aims to determine whether there training of gratitude effect to increase acceptance of parents of mentally retarded children. The hypothesis this study is be influence training of gratitude in improving acceptance of parents terhadap children with mental retardation. Subjects in this study were five parents of children with mental retardation and had the reception was to very low. Measuring instruments used are revenue parent scale. The research method used was a quasi-experimental design with non-equivalent group design. T test using the Mann-Whitney U Test. Analysis showed a significant difference in post-test results of the experimental group and the control group with Z = -2.619 and p = 0.009 or p <0.05. The data analysis using the Wilcoxon Signed Ranks Test showed a level of acceptance of parental toward children with mental retardation in the experimental group by highly significant between before treatment (pretest) and after the treatment (post-test) with Z = -2.032 and p = 0.042 or p <0.05. In contrast to the control group there was no difference in the level of acceptance of the parents at the time of pre-test and post-test. Different test using the Mann-Whitney U Test indicating showed a significant difference in post-test results of the experimental group and the control group with Z = -2.619 and p = 0.009 or p <0.05. It can be concluded that this hypothesis is accepted.